1998
DOI: 10.1038/26026
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of CD8+ T cells is mediated by macrophages through interaction of HIV gp120 with chemokine receptor CXCR4

Abstract: CD8-positive T cells are thought to play an important role in the control of infection by human immunodeficiency virus (HIV) as a result of their cytotoxic activity and by releasing soluble factors. In AIDS patients, the absolute number of CD8+ T lymphocytes is decreased in peripheral blood and their turnover rate is increased, suggesting that there is more cell renewal and cell death occurring. Anti-retroviral therapy raises CD8+ T-cell counts in HIV-infected patients. Here we report that the death rate of CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
304
3
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 390 publications
(322 citation statements)
references
References 26 publications
13
304
3
2
Order By: Relevance
“…[48][49][50][86][87][88][89][90][91][92][93][94] Other members of the TNF-receptor ligand family (TRAIL, TNF-a) have also been implicated in the increased T-cell apoptosis seen in HIV-1-infected individuals. [95][96][97][98][99][100] Similarly, T cells from macaques infected with a pathogenic strain (SIVmac251) are more prone to undergo apoptosis following ligation of CD95/Fas than the other death receptors. 101 Moreover, in HIV-infected individuals and SIV-infected macaques, increased CD95/Fas sensitivity of CD8 þ T cells did not correlate with plasma viral load.…”
Section: Activation-induced Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…[48][49][50][86][87][88][89][90][91][92][93][94] Other members of the TNF-receptor ligand family (TRAIL, TNF-a) have also been implicated in the increased T-cell apoptosis seen in HIV-1-infected individuals. [95][96][97][98][99][100] Similarly, T cells from macaques infected with a pathogenic strain (SIVmac251) are more prone to undergo apoptosis following ligation of CD95/Fas than the other death receptors. 101 Moreover, in HIV-infected individuals and SIV-infected macaques, increased CD95/Fas sensitivity of CD8 þ T cells did not correlate with plasma viral load.…”
Section: Activation-induced Cell Deathmentioning
confidence: 99%
“…149 Apoptosis involve the interaction between several death receptors (Fas, TNF-R, TRAIL-R) and their counterparts, their death ligands. 96,100,102,[150][151][152][153] As tissue macrophages from HIV-infected individuals have been shown to harbor the virus and have the potential to act as reservoirs of virions, the role of macrophages in inducing T-cell death in vivo merit to be further explored in particular regarding pathogenic and nonpathogenic primate models of AIDS. Recently, it has been also observed that incubation of resting CD4 þ T cells from healthy donors with HIV, even in the presence of an inhibitor of the viral replication, is sufficient to prime CD4 þ T cells for apoptosis.…”
Section: Cell Cycle Dysregulationmentioning
confidence: 99%
“…76,59 Bystander Tcell killing can also be mediated by macrophages since ligation of the chemokine receptor CXCR4 by HIV gp120 or its ligand SDF-1 on macrophages induces membrane expression of TNF-a, which triggers apoptosis on TNFRII-expressing CD8 þ T cells. 45 Extracellular Nef protein targets CD4 þ T cells for apoptosis by interacting with CXCR4 surface receptors. Two apoptotic motifs were identified on Nef, the removal of which completely eliminated the ability of Nef to induce apoptosis while retaining Nef ability to enhance viral infectivity.…”
Section: Apoptosis In Hiv-infected Cells and Influence Of Hiv Productsmentioning
confidence: 99%
“…66 HIV therefore can be detrimental to HIV-specific cytotoxic CD8 þ T-cell function in two manners: through inhibition of CD95/Fas-mediated apoptosis of HIVinfected cells, 67 which makes these cells resistant to killing, and the induction of HIV-specific CD8 þ T-cell apoptosis upon contact with CD95L/FasL-expressing HIV-infected cells [68][69][70] ( Figure 1). Interaction of HIV gp120 with the chemokine receptor CXCR4 on macrophages can induce apoptosis of CD8 þ T cells by a TNFR-mediated mechanism, 71 providing another 'fighting back' mechanism for HIV virus if HIV-specific CD8 þ T cells are sensitive to such TNFR-mediated apoptosis. A similar phenomenon has been recently described for HCMV, where the virus can induce apoptosis of virus-specific CD8 þ T cells through the action of CD95/Fas and TRAIL.…”
Section: Apoptotic Defect Of Hiv-specific Cd8 þ T Cells Apoptosis Affmentioning
confidence: 99%
“…126 As the disease progresses, T-tropic (X4) virus strains that bind CXCR4 become predominant, potentially contributing to CD8 þ T-cell loss in late stages of the disease. 71,127 In contrast to CXCR4, CCR5 engagement by gp120 induced in vitro apoptosis only in CD4 þ T cells. 124 However, the contribution of such a mechanism to the in vivo apoptosis of HIV-specific CD8 þ T cells cannot be excluded.…”
Section: Proapoptotic Activity Of Hiv Proteinsmentioning
confidence: 99%